2009
DOI: 10.1007/s10803-009-0849-6
|View full text |Cite
|
Sign up to set email alerts
|

BASC-2 PRS Profiles for Students with High-Functioning Autism Spectrum Disorders

Abstract: BASC-2 PRS profiles of 62 children with high-functioning autism spectrum disorders (HFASDs) were compared with those of 62 typically-developing children matched by age, gender, and ethnicity. Results indicated that, except for the Somatization, Conduct Problems, and Aggression scales, significant differences were found between the HFASD and typically-developing groups on all PRS scores. Mean HFASD scores were in the clinically significant range on the Behavioral Symptoms Index, Atypicality, Withdrawal, and Dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 34 publications
9
86
1
Order By: Relevance
“…26 If future studies support this finding of a particularly strong response on the BASC-2 Atypicality scale to this RR approach, it suggests that this intervention had an unexpected effect on a core symptom of autism, assessed by the BASC-2 Atypicality scale (peculiar, odd, asocial, and inappropriate behaviors, as well as unusual visual perceptions). 26 Of note, the change score was 9 T-score points among the latency-aged children on this scale, rendering this both a statistically and clinically meaningful change.…”
Section: Fig 2 Mean Changes On the The Behavioral Assessmentmentioning
confidence: 86%
See 2 more Smart Citations
“…26 If future studies support this finding of a particularly strong response on the BASC-2 Atypicality scale to this RR approach, it suggests that this intervention had an unexpected effect on a core symptom of autism, assessed by the BASC-2 Atypicality scale (peculiar, odd, asocial, and inappropriate behaviors, as well as unusual visual perceptions). 26 Of note, the change score was 9 T-score points among the latency-aged children on this scale, rendering this both a statistically and clinically meaningful change.…”
Section: Fig 2 Mean Changes On the The Behavioral Assessmentmentioning
confidence: 86%
“…The authors examined its three clinical composite indices (the Externalizing Scale, Internalizing Scale, and Behavioral Symptom Index or BSI), which comprise nine subscales, which were also examined: (1) Aggression, (2) Anxiety, (3) Attention problems, (4) Atypicality, (5) Conduct problems, (6) Depression, (7) Hyperactivity, (8) Somatization, and (9) Withdrawal subscales. A number of studies have supported the scale's structural and validity properties in children who have disruptive behavior 27 and in assessing the unusual thoughts and attention symptoms in children with an ASD, 26,28,29 epilepsy, 30 and for its use with preschool children. 31 The BASC-2 has agespecific child, parent, and teacher self-rating forms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BASC-2 is a standardized measure of clinical concern (i.e., anxiety) and adaptive skills (i.e., social skills) used to help identify typically occurring childhood and adolescent clinical diagnoses (Tan, 2007). It has been utilized in a number of studies involving children with ASD (e.g., Mahan & Matson, 2011;Volker et al, 2010). Parents completed the 150-item Parent Rating Scale, providing four general composites: Externalizing Behaviors, Internalizing Behaviors, Adaptive Behaviors, and Behavioral Symptoms Index.…”
Section: Parent Report Outcome Measuresmentioning
confidence: 99%
“…Individuals with ASDs can exhibit marked differences in their adaptive skills compared with non-affected peers [7 -10] as well as in comparison to those with other disabilities [11 -13] . For example, Volker et al [9] found large differences between individuals with high functioning ASD (HFASD) compared with a neurotypical control group on all of the BASC-2 Parent Rating Scale (BASC-2-PRS) adaptive behavior scales. Specifically, individuals with HFASD were nearly 1.5 standard deviations below their neurotypical peers in the area of Social Skills.…”
Section: Introductionmentioning
confidence: 99%